Atrioventricular Nodal Reentrant Tachycardia in Implantable Cardioverter Defibrillators: Diagnosis and Troubleshooting. (11th September 2015) - ENRIQUEZ, ANDRES; ELLENBOGEN, KENNETH A.; BOLES, USAMA; BARANCHUK, ADRIAN
AVNRT in ICDs: Inappropriate therapies are frequent in patients with implantable cardioverter defibrillators (ICDs) and are associated with adverse outcomes, including increased mortality. Atrioventricular nodal reentrant tachycardia (AVNRT) is the most common reentrant supraventricular tachycardia (SVT) and a cause of inappropriate therapies in these patients. In the present article we review the problem of AVNRT in ICD patients with a focus on diagnosis and the available algorithms to improve arrhythmia discrimination and prevent inappropriate shocks.